Assessment of seismic building vulnerability using rapid visual screening method through web-based application for Malaysia - Kassem M.M.; Beddu S.; Ooi J.H.; Tan C.G.; El-Maissi A.M.; Nazri F.M. (MDPI, 2023)
Rapid visual screening is a quick and simple approach often used by researchers to estimate the seismic vulnerability of buildings in an area. In this study, preliminary seismic vulnerability assessment of 500 buildings situated at Northern and Eastern George Town, Malaysia, was carried out by utilizing a modified FEMA-154 (2002) method that suits Malaysian conditions. Data were collected from online sources via Google Maps and Google Earth instead of traditional surveying data collection through street screening. The seismic assessment analysis of this study was based on the RVS performance score and the damage state classification for each building typology. This approach generates, for each building, a final performance score based on governing parameters such as structural resisting system, height, structural irregularities, building age, and soil type. The findings revealed the immediate need for effective seismic mitigation strategies, as 90% of the studied buildings required a further detailed analyses to pinpoint their exact seismic vulnerability performance. Most of the surveyed buildings were predicted to experience moderate-to-substantial damage, with 220 out of 500 being classed as damage state 2 (D2) and damage state 3 (D3). A GIS map, RVS Malaysian Form-George Town Area, was generated via ArcGIS and shared with the public to provide vital information for further research. 2021 by the authors. Licensee MDPI, Basel, Switzerland.